2019
DOI: 10.1136/gutjnl-2019-318556
|View full text |Cite
|
Sign up to set email alerts
|

International Cancer Microbiome Consortium consensus statement on the role of the human microbiome in carcinogenesis

Abstract: ObjectiveIn this consensus statement, an international panel of experts deliver their opinions on key questions regarding the contribution of the human microbiome to carcinogenesis.DesignInternational experts in oncology and/or microbiome research were approached by personal communication to form a panel. A structured, iterative, methodology based around a 1-day roundtable discussion was employed to derive expert consensus on key questions in microbiome-oncology research.ResultsSome 18 experts convened for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 61 publications
3
154
0
3
Order By: Relevance
“…In addition, Coker et al also revealed CRCassociated mycobiome dysbiosis characterized by altered fungal composition and ecology, signifying that the gut mycobiome might also play a role in CRC development [5]. Recently, an international panel of experts from International Cancer Microbiome Consortium delivered a consensus statement on the role of the human microbiome in carcinogenesis [17], which emphasized that future studies should provide direct evidence to demonstrate the roles of the human commensal microbiome in the aetiopathogenesis of cancer including CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Coker et al also revealed CRCassociated mycobiome dysbiosis characterized by altered fungal composition and ecology, signifying that the gut mycobiome might also play a role in CRC development [5]. Recently, an international panel of experts from International Cancer Microbiome Consortium delivered a consensus statement on the role of the human microbiome in carcinogenesis [17], which emphasized that future studies should provide direct evidence to demonstrate the roles of the human commensal microbiome in the aetiopathogenesis of cancer including CRC.…”
Section: Introductionmentioning
confidence: 99%
“…It brought to our attention that Atopobium and Fusobacterium were identi ed as sarcoidosis-associated bacteria, which may enable new insights into the pathogenesis and treatment of CRC [12]. In CRC, the abundance of Atopobium parvulum and Actinomyces odontolyticus, were signi cantly increased only in multiple polypoid adenomas and/or intramucosal carcinomas, indicating those two bacteria may be considered as the microbiome therapy target in CRC [13]. These studies provided evidence that not only the single effect, but also synergistic effects of Atopobium with other gut microbiota such as Fusobacterium, Stomatobaculum,and Actinomyces may lead to different clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…With any such reported association, a cause-and-effect question is raised: do microbiome variations play a role in disease causation or is it just an association that could merely be used as a biomarker for the adverse health outcome (Maruvada et al, 2017;Rosato et al, 2018). For example, causation has been demonstrated in inflammatory bowel diseases (Moustafa et al, 2018) and colorectal cancer (Tjalsma et al, 2012;Scott et al, 2019).…”
Section: The Microbiome Cloud In Health and Diseasementioning
confidence: 99%
“…Using such biomarkers as non-invasive alternatives to biopsies and endoscopy, for example, would be a promising futuristic diagnostic (Ren et al, 2019) and predictive/preventive tool (Penalver Bernabe et al, 2018). For example, the human microbiota was found to release molecules and metabolites that affect the onset, progression, and treatment of cancer (Scott et al, 2019;Rao et al, 2020). True personalized cancer therapy may only be achieved through a full understanding of the effect of microbiome on chemotherapy (Table 2) and tumorigenesis, thus allowing proper patient stratification-based on specific biomarkers, microbiome types, and metabotypes (Rizkallah et al, 2010;Kuntz and Gilbert, 2017).…”
Section: Microbiome Biomarkers As Future Non-invasive Tools In Precismentioning
confidence: 99%